Importance of environmental productivity and diet quality in intraguild predation - Toshiyuki Namba; Yasuhiro Takeuchi; Malay Banerjee (Theoretical Population Biology, 2025)

Dynamical study on volatiles signaling in plant disease and pest-natural enemy interaction - Ritwika Mondal; Yasuhiro Takeuchi; Dipak Kesh; Debasis Mukherjee (Modeling Earth Systems and Environment, 2025)

Airborne hydrophilic microplastics in cloud water at high altitudes and their role in cloud formation - Yize Wang; Hiroshi Okochi; Yuto Tani; Hiroshi Hayami; Yukiya Minami; Naoya Katsumi; Masaki Takeuchi; Atsuyuki Sorimachi; Yusuke Fujii; Mizuo Kajino; Kouji Adachi; Yasuhiro Ishihara; et al. (Environmental Chemistry Letters, 2023)
Microplastic pollution is occurring in most ecosystem, yet their presence in high altitude clouds and their influence on cloud formation and climate change are poorly known. Here we analyzed microplastics in cloud water sampled at the summits of Japan mountains at 1300–3776 m altitude by attenuated total reflection imaging and micro-Fourier transform infrared spectroscopy. We observed nine microplastics including polyethylene, polypropylene, polyethylene terephthalate, polymethyl methacrylate, polyamide 6, polycarbonate, ethylene–propylene copolymer or polyethylene–polypropylene alloy, polyurethane, and epoxy resin. Microplastic were fragmented, with mean concentrations ranging from 6.7 to 13.9 pieces per liter, and with Feret diameters ranging from 7.1 to 94.6 μm. Microplastics bearing hydrophilic groups such as carbonyl and/or hydroxyl groups were abundant, suggesting that they might have acted as condensation nuclei of cloud ice and water. Overall, our finding suggest that high-altitude microplastics cloud influence cloud formation and, in turn, might modify the climate.

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Effect of a proton-pump inhibitor on intestinal microbiota in patients taking low-dose aspirin - Hiroyuki Tsujimoto; Yuki Hirata; Yasuhiro Ueda; Naohiko Kinoshita; Hideki Tawa; Yasuyoshi Tanaka; Ryoji Koshiba; Kazuhiro Ota; Yuichi Kojima; Kazuki Kakimoto; Toshihisa Takeuchi; Takako Miyazaki; et al. (European Journal of Clinical Pharmacology, 2021)

HEK293 cells express dystrophin Dp71 with nucleus-specific localization of Dp71ab - Atsushi Nishida; Sato Yasuno; Atsuko Takeuchi; Hiroyuki Awano; Tomoko Lee; Emma Tabe Eko Niba; Takahiro Fujimoto; Kyoko Itoh; Yasuhiro Takeshima; Hisahide Nishio; Masafumi Matsuo (Histochemistry and Cell Biology, 2016)

Lactoferrin Conjugated with 40-kDa Branched Poly(ethylene Glycol) Has an Improved Circulating Half-Life - Yasuhiro Nojima; Yosuke Suzuki; Kazuhiro Yoshida; Fumiko Abe; Tuneo Shiga; Takashi Takeuchi; Akihiko Sugiyama; Hirohiko Shimizu; Atsushi Sato (Pharmaceutical Research, 2009)

Coleoptile cuticle of barley is necessary for the increase in appressorial turgor pressure of Blumeria graminis for penetration - Mana Iwamoto; Yoji Takeuchi; Yasuhiro Takada; Shintaro Kohno; Isao Matsumoto; Naoto Yamaoka (Journal of General Plant Pathology, 2007)

Effect of light irradiation on dynamics of vitamin A compounds in rotifers and Artemia - Yutaka HAGA; Fuminori TARUI; Kengo OHTA; Yasuhiro SHIMA; Toshio TAKEUCHI (Fisheries Science, 2006)

Effect of Artemia nauplii enriched with vitamin A palmitate on hypermelanosis on the blind side in juvenile Japanese flounder Paralichthys olivaceus - Fuminori TARUI; Yutaka HAGA; Kengo OHTA; Yasuhiro SHIMA; Toshio TAKEUCHI (Fisheries Science, 2006)

Defense responses of Arabidopsis thaliana inoculated with Pseudomonas syringae pv. tabaci wild type and defective mutants for flagellin (ΔfliC) and flagellin-glycosylation (Δorf1) - Yasuhiro Ishiga; Kasumi Takeuchi; Fumiko Taguchi; Yoshishige Inagaki; Kazuhiro Toyoda; Tomonori Shiraishi; Yuki Ichinose (Journal of General Plant Pathology, 2005)

Structural studies on IgG oligosaccharides of patients with primary Sjögren's syndrome - Yasuhiro Kuroda; Munehiro Nakata; Ayako Makino; Ayano Matsumoto; Kazuhiro Ohashi; Koju Itahashi; Fujio Takeuchi; Makoto Goto; Naoya Kojima; Tsuguo Mizuochi (Glycoconjugate Journal, 2002)

Urinary 2,5-hexanedione increases with potentiation of neurotoxicity in chronic coexposure to n -hexane and methyl ethyl ketone - Gaku Ichihara; Isao Saito; Michihiro Kamijima; Xiaozhong Yu; Eiji Shibata; Machiko Toida; Yasuhiro Takeuchi (International Archives of Occupational and Environmental Health, 1998)

Pulmonary metal distribution in urban dwellers - Fumi Tsuchiyama; Naomi Hisanaga; Eiji Shibata; Takeshi Aoki; Hiromi Takagi; Tatsushi Ando; Yasuhiro Takeuchi (International Archives of Occupational and Environmental Health, 1997)

Effects of MEK on kinetics ofn-hexane metabolites in serum - Eiji Shibata; Jian Huang; Naomi Hisanaga; Yuichiro Ono; Isao Saito; Yasuhiro Takeuchi (Archives of Toxicology, 1990)

Effects of chronic n-hexane exposure on nervous system-specific and muscle-specific proteins - Jian Huang; Kanefusa Kato; Eiji Shibata; Kimiya Sugimura; Naomi Hisanaga; Yuichiro Ono; Yasuhiro Takeuchi (Archives of Toxicology, 1989)